EGMR 41723/14 vom 22. Dezember 2020 , CASE OF SCHWEIZERISCHE RADIO- UND FERNSEHGESELLSCHAFT AND PUBLISUISSE SA v. SWITZERLAND - [German Translation] by the Austrian Institute for Human Rights (ÖIM) - Hudoc Ch (2020)
No violation of Article 10 - Freedom of expression-{general} (Article 10-1 - Freedom of expression); No violation: 10;10-1